Schwarz-Christoffel mapping - Driscoll, Tobin A. (Tobin Allen), 1969- (Cambridge monographs on applied and computational mathematics, 2002)
This book provides a comprehensive look at the Schwarz-Christoffel transformation, including its history and foundations, practical computation, common and less common variations, and its many applications. It is intended as an accessible resource for engineers, scientists, and applied mathematicians who may not have much prior experience with theoretical or computational conformal mapping techniques.